Метод компенсації нелінійностей, що можуть відділятись від лінійної частини об'єкта електромеханічної системи - Садовой, Олександр Валентинович; Шеремет, Олексій Іванович (НТУ "ХПІ", 2010)
Indemnification method of nonlinearities is considered, allowing to eliminate influence of any nonlinearity on system, but this nonlinearity must be separate from a linear part of object, i.e. the signal before and after it must be accessible to measurement or calculation.
Indemnification method of nonlinearities which can separate from a linear part of electromechanical system object
Keywords: функція дискретна; керування; сигнал; модель математична